Factors of Affecting Tax Avoidance in The Property and Real Estate Sector 2017-2020 - Wati Yaramah; Nur Alvisyahri Nazila (EAJ (Economic and Accounting Journal), 2022)
Tax avoidance is a legal strategy used by taxpayers to decrease their tax liabilities, safely and without violating tax laws. But the reality is that many taxpayers deviate from the rules to carry out this tax avoidance. The goal of the research is to gather empirical evidence on tax avoidance profitability, leverage, capital intensity, and institutional ownership. The population in this study is a real &estate property sector company listed on the Indonesia Stock Exchange for 2017 - 2020. The sample selection technique uses purposive sampling and obtained by 9 companies with a time of 4 years so that 36 samples were observed. The data analysis model in this study is regression of panel data using Eviews Software 11.0. The results showed that profitability, leverage, capital intesity and institutional ownership had simultaneous influences on tax avoidance. Studies indicate institutional ownership has a negative and significant impact on tax avoidance. Capital intensity has a positive impact on tax avoidance, while profitability and leverage have no effect on tax avoidance.